2022
DOI: 10.1002/ajoc.202200610
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐catalyzed Decarbonylation of Acylsilanes

Abstract: The rhodium-catalyzed decarbonylation of acylsilanes is reported. This reaction proceeds through the cleavage of a carbon-silicon bond in acylsilanes. When two different acylsilanes are reacted in one batch, crossover products are formed. These results indicate that two mechanisms are operating in this catalytic reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This is presumably because C­(O)–Si bonds are weaker than C­(O)–C­(aryl) bonds, which allows the nickel species to maintain its activity in the presence of CO. Quite recently, Tobisu et al also reported a rhodium-catalyzed variant in which BrettPhos serves as an appropriate ligand. (Scheme B-iii) . This study showcases the capability of a rhodium­(I) complex to facilitate the oxidative addition of C­(O)–Si bonds in acylsilanes.…”
Section: Elimination Of Co From Carbonyl Compounds (Decarbonylation)mentioning
confidence: 71%
See 1 more Smart Citation
“…This is presumably because C­(O)–Si bonds are weaker than C­(O)–C­(aryl) bonds, which allows the nickel species to maintain its activity in the presence of CO. Quite recently, Tobisu et al also reported a rhodium-catalyzed variant in which BrettPhos serves as an appropriate ligand. (Scheme B-iii) . This study showcases the capability of a rhodium­(I) complex to facilitate the oxidative addition of C­(O)–Si bonds in acylsilanes.…”
Section: Elimination Of Co From Carbonyl Compounds (Decarbonylation)mentioning
confidence: 71%
“…(Scheme 15B-iii). 89 This study showcases the capability of a rhodium(I) complex to facilitate the oxidative addition of C(�O)−Si bonds in acylsilanes.…”
Section: Acylsilanesmentioning
confidence: 82%
“…(Scheme A). We also reported that, when alkenes are used, the oxidative addition intermediate is isomerized to a siloxycarbene–palladium complex, which then undergoes cyclopropanation with alkenes , and carbonylative cycloaddition with imines. , We report herein on the use of fluorinated acylsilanes in these palladium-catalyzed addition reactions, which allow access to a range of fluorinated organosilicon compounds (Scheme B). This expansion will find numerous applications in organic synthesis, given that the introduction of a trifluoromethyl (CF 3 ) group into an organic molecule dramatically improves the bioactivity or metabolic stability of pharmaceuticals and agrochemicals .…”
mentioning
confidence: 99%
“…Unimolecular fragment coupling (UFC) is defined as the reaction format, in which the linker of a molecule is eliminated and the remaining fragments are then coupled. Typical examples include the decarboxylation of esters or the decarbonylation of carbonyl compounds . UFC reactions are potentially valuable methods because readily available starting materials are used and no other reagents, except for catalysts, are required, thus making it suitable for late-stage bond formation.…”
mentioning
confidence: 99%